The management of specialized information services conceived as an enlarged enterprise - Arboleda Sepúlveda, Orlando (2005)
The extended enterprise concept, within service management, makes it possible to analyze the functions and objectives of libraries, take advantage of opportunities and overcome constraints that have traditionally been a cause for stagnation. The economy of services and advances in information systems technology require libraries to play a more aggressive role in identifying with the mission, vision and objectives of the organizations to which they belong. Applying the concept of an expanded enterprise could allow libraries to achieve the benefits of a network of value, as opposed to the disadvantages of working in isolation from their internal, external and final clients.